Prototype of a Spring-Loaded Module for Axillary Crutches - Dalia Danely Méndez-Gómez; Arturo Minor-Martínez; Salvador Montoya-Alvarez; Fernando Pérez-Escamirosa; Jessica Cantillo-Negrete (Sensors)
Axillary crutches assist people with lower limb injuries but can lead to upper limb strain with extended use. Spring-loaded crutches offer a potential solution, yet they are rarely tested in clinical settings. This study developed spring-loaded crutches with an integrated force-measuring system to analyze gait dynamics. Three prototypes, each with different spring constants (k), were tested. To measure ground reaction force (GRF), a Nylamid cover was around the crutch stem. Two participants with different weights completed a 15-m route using both the designed spring-loaded and standard crutches. Findings showed that spring-loaded crutches increased mean GFR and impulse, with the prototype matched to the user’s weight yielding the best results. The study’s findings suggest that when properly adjusted to the user’s weight, spring-loaded crutches can offer significant improvements in gait, which may have important implications for the design of mobility assistive devices.